Postoperative Pancreatic Fistula: A Surgeon’s Nightmare! An Insight with a Detailed Literature Review - Seetharam, Prasad; Rodrigues, Gabriel Sunil (JOP. Journal of the Pancreas, 2015)
Context Postoperative fistula formation is an important complication following pancreatic resections. Objective A large volume of literature without uniform conclusions is available regarding various controversies about postoperative pancreatic fistulae. The term postoperative pancreatic fistula includes fistula resulting from any surgery involving pancreas, most commonly pancreaticoduodenectomy and distal pancreatectomy. In this review, we have tried to present a comprehensive account of postoperative pancreatic fistula with particular emphasis on important controversies clouding the subject. Methods We performed MEDLINE literature search for relevant articles using the key words pancreas, pancreatic cancer, pancreatectomy, pancreatoduodenectomy, Whipple’s operation, postoperative, complications, fistula, management and treatment in various combinations with the Boolean operators AND, OR and NOT. Conclusions Postoperative pancreatic fistula is a troublesome complication of pancreaticoduodenectomy. Although the risk factors for postoperative pancreatic fistula have been extensively described, none of the methods recommended for preventing postoperative pancreatic fistula have been conclusively proved to be effective. While endoscopic treatment and percutaneous treatment form important aspects of treatment of postoperative pancreatic fistula, surgery may be required for select cases. Image: Management of postoperative pancreatic fistula.